ANALISIS EFEKTIVITAS REZIM INTERNASIONAL CEDAW DALAM IMPLEMENTASINYA DI INDONESIA - Ferry Mario Zakaria Ngelo; Winona Albertha; Tiara Azka Azkia; Yusriyatun Najwa; Aurellia Neiva Wicialyn Lutter (Jurnal Humaniora & Sosial Sains, 2025)
Gender equality is a global issue that continues to be pursued, including in Gender equality is a global issue that continues to be pursued, including in Indonesia. This study aims to analyze the effectiveness of implementing the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW), which Indonesia ratified in 1984. Using a descriptive-qualitative approach and the theoretical framework of international regimes, the study evaluates the successes, challenges, and opportunities in implementing CEDAW principles. The data analyzed include government reports, UN documents, national statistics, and academic journals. The findings reveal that despite legislative progress, such as the enactment of the Sexual Violence Law (UU TPKS) and gender mainstreaming policies, substantive implementation remains constrained. Key obstacles include patriarchal cultural norms, limited capacity of law enforcement agencies, and low public awareness. These findings underscore the necessity of cross-sectoral collaboration to enhance the effectiveness of CEDAW-based policies. This study contributes to the literature by offering strategic recommendations to strengthen CEDAW implementation and achieve sustainable gender equality in Indonesia.